2017
DOI: 10.1007/s11104-017-3195-z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Bacillus altitudinis JSCX-1 as a new potential biocontrol agent against Phytophthora sojae in soybean [Glycine max (L.) Merr.]

Abstract: Aims Phytophthora root and stem rot caused by the oomycete plant pathogen Phytophthora sojae (Kaufmann & Gerdemann), is a destructive disease of soybean [Glycine max (L.) Merr.]. There is no straightforward available method to control this disease. The present study aimed to isolate a biocontrol agent (BCA) to control Phytophthora rot and gain insights into the mechanisms of biocontrol activity. Methods Antagonistic bacteria screening, inoculation assays, histochemical and fluorometric staining and real-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 77 publications
3
43
0
Order By: Relevance
“…There are several studies about improving growth dynamics and increased availability of nutrients in the rhizosphere (Patten and Glick 2002). It is clearly observed that B.subtilis and T. harzianum treatments and essential oils caused sharp increase in vegetative growth such as plant height, branches, leaves number, and oil yield (Lu et al 2017;Sadeghi et al 2017;Omara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies about improving growth dynamics and increased availability of nutrients in the rhizosphere (Patten and Glick 2002). It is clearly observed that B.subtilis and T. harzianum treatments and essential oils caused sharp increase in vegetative growth such as plant height, branches, leaves number, and oil yield (Lu et al 2017;Sadeghi et al 2017;Omara et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, biological control and essential oils provide an ecofriendly solution alternative to chemical control. For biological control, several microbes like Bacillus pumilus, B.subtilis and B.licheniformis as well as Trichoderma viride and Pseudomonas species have been considered as a biocontrol agents against pathogens through their ability to serve as a source of bioactive compounds and plant growth promoting such as antibiotic production, colonization site competition, production of hydrogen cyanide, hydrolytic enzymes, siderophores, ammonia, fluorescent pigments and/or antimicrobial volatiles (Keshavarz-Tohid et al 2017;Sadeghi et al 2017;Lu et al 2017;Omara et al 2018). For essential oils like Pelargonium roseum, Carum carvi, Pimenta dioica, Cymbopogon nardus and Thymus vulgaris have been considered antifungal activity which may be attributed to their major ingredients or a synergistic or antagonistic effect with various compounds.…”
Section: Management Of Charcoal Rot (Macrophomina Phaseolina) Infectimentioning
confidence: 99%
“…18 Among them, Bacillus is frequently reported as a potential biofertilizer due to its multi-functional PGP traits, such as phosphate solubilization, 13 , 14 indole-acetic acid (IAA) production, 10 , 13 siderophore (iron chelator) production, 19 and biocontrol ability against plant pathogens. 20 In addition, biofertilizers containing Bacillus strains are considered important because of their spore-forming capacity, allowing their adaptation to extreme abiotic conditions, such as extreme temperatures, pH, or pesticide exposure. 14 Bacillus species have shown to positively affect soybean seed germination by enhancing significantly the root and shoot length, or number of lateral root of the seedling.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these Bacillus spp. are associated with plants and were reported to have potential application in biomedicine and biocontrol (Liu et al, 2019;Lu et al, 2017;Jouzani et al, 2017;Prazdnova et al, 2019;Wang et al, 2017) as well as potential probiotics (Elshaghabee et al, 2017) and biofertilizer (Pramanik et al, 2019). Lysinibacillus and Paenibacillus are widespread bacteria usually considered as environmental contaminants and rarely connected to human diseases (Wenzler et al, 2015;Sannino and Angert, 2017).…”
Section: Microbial Ecology In Pot-pollen Samplesmentioning
confidence: 99%